The impact of globalization on the characteristics of European countries’ tax systems - Luković Stevan (Ekonomski Anali, 2015)
In the international literature, a great number of studies have sought to determine the relationship between the characteristics of the national tax systems and globalization. Most of the research was conducted to prove the impact of the tax system on the competitiveness of the national economy, in order to give a clear recommendation for how economic and fiscal policy should create a stimulating economic background and enable greater involvement of the national economy in international flows. However, the process can be viewed from the reverse perspective, in the sense that the process of globalization and international competition can shape the characteristics of national tax systems. This paper aims to determine by empirical evidence the impact of the process of globalization and international competition on the characteristics of taxation in observed European countries.